If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12(x+4)=420
We move all terms to the left:
-12(x+4)-(420)=0
We multiply parentheses
-12x-48-420=0
We add all the numbers together, and all the variables
-12x-468=0
We move all terms containing x to the left, all other terms to the right
-12x=468
x=468/-12
x=-39
| (2X+3)(5x^2-12x+7)=0 | | 18=3m-m | | 1/5(2a-5)-4=1/2(a+4)=7/10 | | 3(x+5)=6-3(2x+4) | | 7y-8-6y=+1 | | -8.5x+0.51=-6.29 | | 28=10x-3x | | X-5×x=84 | | 3(5x+6)+4(6x+3)+6=39x+37 | | e/4-3=3 | | 2+y/2+4y/5=y-2/3 | | n/6+12=-8 | | 2m-25=8m+13 | | 9=q–4 | | 4z7+7=-7 | | 89=8x | | 7q-3=18 | | 12(2k+11=12(2k+12) | | 60^s+80s=-25 | | 3/4b-4=-7/8b+1 | | 46-5a=10-9a | | (4m+2)(3m-2)=0 | | -11(d+7)=11 | | -11b=7+40 | | 16)8(11-x)=16 | | x+17=22–22 | | 3^2x=6651 | | 24x-24=24x+24 | | 15)7(2+x)=35 | | 1/6x+1/8=27/8 | | 9-2x-(2x^-1/2)=0 | | 14)9(x+9)=90 |